Sustaining Innovation: Theory and Policies for new Europe - Samonis, Valdas (Val) (Ekonomika, 2004)
The paper attempts to propose a theoretical frame needed to sustain innovation processes in the enlarged European Union. Sustainable innovation processes are seen in the paper as the main driver of competitiveness (and therefore productivity) in the European Union, as called for by the Lisbon Strategy in 2000. Actionable policy and business strategy implications of the proposed theoretical frame are also outlined using a knowledge management perspective. They center on the cluster method of modern development as proposed by Harvard’s Prof. M. Porter. Suggestions for further and related research are also included in the paper.